Boosting CO2 Photoreduction via Regulating Charge Transfer Ability in a One‐Dimensional Covalent Organic Framework - Zou, Lei; Chen, Zi‐Ao; Si, Duan‐Hui; Yang, Shuai‐Long; Gao, Wen‐Qiang; Wang, Kai; Huang, Yuan‐Biao; Cao, Rong (Angewandte Chemie International Edition, 2023)
Two‐dimensional (2D) imine‐based covalent organic frameworks (COFs) hold potential for photocatalytic CO2 reduction. However, high energy barrier of imine linkage impede the in‐plane photoelectron transfer process, resulting in inadequate efficiency of CO2 photoreduction. Herein, we present a dimensionality induced local electronic modulation strategy through the construction of one‐dimensional (1D) pyrene‐based covalent organic frameworks (PyTTA‐COF). The dual‐chain‐like edge architectures of 1D PyTTA‐COF enable the stabilization of aromatic backbones, thus reducing energy loss during exciton dissociation and thermal relaxation, which provides energetic photoelectron to traverse the energy barrier of imine linkages. As a result, the 1D PyTTA‐COF exhibits significantly enhanced CO2 photoreduction activity under visible‐light irradiation when coordinated with metal cobalt ion, yielding a remarkable CO evolution of 1003 μmol g−1 over an 8‐hour period, which surpasses that of the corresponding 2D counterpart by a factor of 59. These findings present a valuable approach to address in‐plane charge transfer limitations in imine‐based COFs. One‐dimensional pyrene‐based covalent organic frameworks (1D PyTTA‐COF) have been applied for CO2 photoreduction for the first time. The stabilization of the aromatic backbone by interchain interaction in 1D PyTTA‐COF improved exciton dissociation and attenuated the thermal relaxation processes of excited photoelectrons, aiding the movement of photoelectrons across the imine linkage to catalytic sites for CO2 conversion.